Respuesta :

Bring like terms together then simplify:-

= 4x^3 + 3x^3 - 3x + 5x + 3 - 7

= 7x^3 + 2x - 4


After performing the addition operation on both expressions, the resulting simplified expression is 7x^3+2x-4

Simplification of Algebra Expression

Given Data

  • First expression =  (4x3 − 3x − 7)
  • Second expression = (3x3 + 5x + 3)

To add both Expression let us open brackets

= (4x3 − 3x − 7) + (3x3 + 5x + 3)

=  4x3 − 3x − 7 + 3x3 + 5x + 3

Collect like terms we have

= 4x^3+3x^3-3x+5x-7+3

= 7x^3+2x-4

Learn more about simplification here:

https://brainly.com/question/2548064

ACCESS MORE